PENGARUH IKLIM ORGANISASI TERHADAP KOMITMEN ORGANISASIONAL DAN RETENSI PEGAWAI KONTRAK DI BAPPEDA LITBANG PROVINSI BALI - Cahyadi, Meliana Kurniawati; Utama, I Wayan Mudiartha (E-Jurnal Manajemen, 2018)
Retention is an essential element of an organizational approach. Each organization should strive to retain its employees, especially employees who have important value for the organization. Maintaining the best professional talent is a very important practice for organizations such as eliminating recruitment, selection and reducing costs of their turnover, and maintaining continuity according to their area of expertise . This study aims to determine the effect of organizational climate on organizational commitment and retention of contract employees in Bappeda Litbang Bali Province by using 66 people as research respondents . Sample determination technique used in this research is using census technique. Data collection was done through interviews and questionnaires. Data analysis technique used in this research is path analysis processed using SPSS software. The results obtained in this study indicate that the organizational climate has a positive and significant relationship to organizational commitment, organizational climate has a positive and significant relationship to organizational retention and climate has a positive and significant relationship to retention. Keyword : organizational climate, organizational commitment, retention